Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41416-020-01158-z
|View full text |Cite
|
Sign up to set email alerts
|

The RNA polymerase I transcription inhibitor CX-5461 cooperates with topoisomerase 1 inhibition by enhancing the DNA damage response in homologous recombination-proficient high-grade serous ovarian cancer

Abstract: Background Intrinsic and acquired drug resistance represent fundamental barriers to the cure of high-grade serous ovarian carcinoma (HGSC), the most common histological subtype accounting for the majority of ovarian cancer deaths. Defects in homologous recombination (HR) DNA repair are key determinants of sensitivity to chemotherapy and poly-ADP ribose polymerase inhibitors. Restoration of HR is a common mechanism of acquired resistance that results in patient mortality, highlighting the need to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Pipier et al found that small interfering RNA (siRNA)-mediated depletion of the TOP2α isoform or inhibition of its catalytic activity confers resistance to CX-5461 [121]. Since CX-5461 has been shown to induce activation of ATR at rDNA indicating nucleolar replication stress [97,122], it is plausible that CX-5461 may carry out its action by potentially trapping TOP2α with high selectivity to rDNA promoters compared to regions across the genome. Indeed, a recent study has shown that CX-5461 may act as a DNA structure-driven TOP2poison at transcribed regions bearing G4 structures [123].…”
Section: Cx-5461 S Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pipier et al found that small interfering RNA (siRNA)-mediated depletion of the TOP2α isoform or inhibition of its catalytic activity confers resistance to CX-5461 [121]. Since CX-5461 has been shown to induce activation of ATR at rDNA indicating nucleolar replication stress [97,122], it is plausible that CX-5461 may carry out its action by potentially trapping TOP2α with high selectivity to rDNA promoters compared to regions across the genome. Indeed, a recent study has shown that CX-5461 may act as a DNA structure-driven TOP2poison at transcribed regions bearing G4 structures [123].…”
Section: Cx-5461 S Mode Of Actionmentioning
confidence: 99%
“…CX-5461 also activates p53-independent ATM/ATR signaling and the G2/M cell cycle checkpoint in high-grade serous ovarian cancer (HGSOC) cells, leading to growth arrest in vitro and in vivo [97,122]. CX-5461 treatment induces RPA phosphorylation and ATR activation within the nucleoli in HGSOC cells, indicating CX-5461 induces replication stress at the rDNA [97].…”
Section: Therapeutic Response To Cx-5461 Is Mediated Via Activation Of the Irbc And The N-ddrmentioning
confidence: 99%
“…Mechanistically, we found that both drugs elicit DNA double-strand breaks, as evaluated by gamma H2AX, but only CX-5461 evoked ATM-driven DNA damage signaling within the cells. Previous studies have shown that treatment with CX-5461 causes substantial cellular DNA damage, leading to activation of the ATM/ATR signaling pathway, which, in turn, activates downstream CHK2/CHK1, resulting in G2/M arrest [ 50 , 51 , 52 ]. However, in our study conditions, the G2/M arrest was not so apparent between the cell lines tested.…”
Section: Discussionmentioning
confidence: 99%
“…5a, b), demonstrating that G4s ligands can compete with CSB for binding to intermolecular rDNA G4s under our experimental conditions. CX-5461 has often been considered a transcriptional inhibitor in previous reports 6,15,37,38 , albeit it has been previously designed and recently further validated as an effective G4-ligand 19 . Our results demonstrate that CX-5461 can outcompete CSB for binding to intermolecular rDNA G4s, suggesting that both the premature ageing phenotype and the CSB nucleolus displacement observed upon treatment with this ligand are more likely due to its G4-binding ability rather than transcriptional inhibition, similarly to what observed with PDS.…”
Section: Csb Binds and Resolves Intermolecular G4smentioning
confidence: 99%